2020
DOI: 10.1200/jco.2020.38.15_suppl.1066
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib trial to evaluate safety and anti-tumor activity of the AKT inhibitor, ipatasertib, in combination with endocrine therapy and a CDK4/6 inhibitor for patients with hormone receptor positive (HR+)/HER2 negative metastatic breast cancer (MBC) (TAKTIC).

Abstract: 1066 Background: The cyclin-dependent kinase 4/6 inhibitors (CDK4/6i), with an anti-estrogen, are the standard of care for HR+/HER2- MBC. Insights from patient biopsies and preclinical analysis suggest that AKT1 activation can provoke CDK4/6i resistance. We hypothesized that targeting AKT1 following CDK4/6i progression may provide clinical benefit. Methods: TAKTIC is an open-label phase Ib trial exploring the combination of the AKT1 inhibitor, ipatasertib (ipat), with an aromatase inhibitor (Arm A), fulvestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Preliminary results on the first 12 patients enrolled in cohort C (ipatasertib + fulvestrant + palbociclib) were reported at ASCO 2020. The triplet showed signals of clinical activity in this heavily pretreated population with proven resistance to CDKIs, with two partial responses and three stable disease registered ( Wander et al, 2020 ). IPATunity150 is a phase III randomized trial with a preliminary safety run-in cohort, which will compare the combination of ipatasertib + fulvestrant + palbociclib and placebo + fulvestrant + palbociclib in a population of endocrine resistant HR + BC, naïve to CDK4/6 inhibitors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Preliminary results on the first 12 patients enrolled in cohort C (ipatasertib + fulvestrant + palbociclib) were reported at ASCO 2020. The triplet showed signals of clinical activity in this heavily pretreated population with proven resistance to CDKIs, with two partial responses and three stable disease registered ( Wander et al, 2020 ). IPATunity150 is a phase III randomized trial with a preliminary safety run-in cohort, which will compare the combination of ipatasertib + fulvestrant + palbociclib and placebo + fulvestrant + palbociclib in a population of endocrine resistant HR + BC, naïve to CDK4/6 inhibitors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Everolimus in combination with Exemestane (BOLERO-2 trial) [87,88] Ipatasertib in combination with endocrine therapy and a CDK4/6 inhibitor (TAKTIC trial) [89] Concurrent inhibition of ERα, CCND1-CDK4/6-RB pathway and the PI3K-AKT-mTOR pathways…”
Section: Drugs In Clinical Developmentmentioning
confidence: 99%
“…Preliminary results of the triplet combination have shown two partial responses amongst 12 patients, and the combination was well tolerated with no dose limiting toxicities at reported dose levels. 96 A phase Ib trial of cobimetinib and ipatasertib was however poorly tolerated and all 66 patients who received study drug reported an adverse event, with 53% experiencing drug-related AE of grade 3 or worse severity, though none were dose-limiting toxicities. Although biomarker analyses indicated blockade of combined RAS/MEK/ ERK and pI3K/AKT/mTOR pathways in paired tumor biopsies, objective responses were only observed in two patients with endometrial cancer and one with ovarian cancer.…”
Section: Ipatasertib (Gdc-0068)mentioning
confidence: 99%
“…Preliminary results of the triplet combination have shown two partial responses amongst 12 patients, and the combination was well tolerated with no dose limiting toxicities at reported dose levels. 96 …”
Section: Combination Strategiesmentioning
confidence: 99%